(untitled) (Scientific journal of the Fergana State University, 2023)
When borrowed into the vocabulary of the media space, anglicisms, like other foreign words, undergo integrative changes. For the further successful functioning of the word in the receiving language, first of all, it is adapted in accordance with the rules of spelling, orthoepy and morphology. In this study, we do not consider the phonetic and graphic development of anglicisms during their transition to the Russian media space. This is due to the fact that most borrowings in the vocabulary of the media space retain their English pronunciation and spelling. In this connection, the article pays special attention to the morphological assimilation of English vocabulary, as well as its inclusion in the word-formation paradigm of the Russian language, typical for the vocabulary of the media space